Regional price dynamics in Argentina (2016-2019) - González, Fernando Antonio Ignacio (2020)
This work investigates compliance with the Law of One Price (LOP) across regions of Argentina. A convergence and cointegration analysis of the 2016–2019 period is conducted using the series of the Total Basic Basket (TBB) and the Consumer Price Index (CPI) published by the National Institute of Statistics and Census (INDEC in Spanish) on a monthly basis for six regions in Argentina. The results suggest the existence of convergence in prices and cointegration across regions, which is consistent with compliance with the LOP. This is especially relevant for its potential impact on regional poverty disparity. Indeed, if poorer regions with lower prices tend to have a greater increase in price levels –and therefore convergence is observed– this may imply an increase in regional disparities.